2022
DOI: 10.1186/s13287-022-03088-4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DNA methyltransferase-3a ameliorates the osteogenic differentiation ability of adipose-derived stem cells in diabetic osteoporosis via Wnt/β-catenin signaling pathway

Abstract: Background Diabetes-related osteoporosis (DOP) is a chronic disease caused by the high glucose environment that induces a metabolic disorder of osteocytes and osteoblast-associated mesenchymal stem cells. The processes of bone defect repair and regeneration become extremely difficult with DOP. Adipose-derived stem cells (ASCs), as seed cells in bone tissue engineering technology, provide a promising therapeutic approach for bone regeneration in DOP patients. The osteogenic ability of ASCs is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…A recent study found that Dnmt3a may inhibit osteoblast differentiation via regulating Wnt/β-catenin signaling and Runx2, Ocn activity (Fig. 5d ; Table 3 ) 422 . Demethylation of the promoter’s CG region is linked to the ten-eleven translocases (TET) protein, which may alter chromatin status and encourage osteoblast differentiation 422 .…”
Section: Epigenetic Modification Of Transcriptional Gene Regulationmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent study found that Dnmt3a may inhibit osteoblast differentiation via regulating Wnt/β-catenin signaling and Runx2, Ocn activity (Fig. 5d ; Table 3 ) 422 . Demethylation of the promoter’s CG region is linked to the ten-eleven translocases (TET) protein, which may alter chromatin status and encourage osteoblast differentiation 422 .…”
Section: Epigenetic Modification Of Transcriptional Gene Regulationmentioning
confidence: 88%
“… 408 DNA methylases Dnmt3a Inhibits osteoblast differentiation via regulating Wnt/β-catenin signaling and Runx2, Ocn activity. 422 DNA demethylases TET1/2 Converts 5mCpG to 5hmCpG. 423 425 Chromatin remodeling Baf45a/ Baf45d Promote the activation of genes crucial for osteoblast maturation and mineralization 415 , 419 , 420 …”
Section: Epigenetic Modification Of Transcriptional Gene Regulationmentioning
confidence: 99%
“…Firstly, although we identified that resistin targeted TAZ to induce OD through PI3K/AKT/mTOR pathway, the crosstalk with other signaling pathways cannot be ruled out, and the interaction between resistin and the OD-related genes remains to be further revealed. We next sought to explore other possible pathways, including Wnt/β-catenin pathway 42 , 43 and MAPK pathway, 44 , 45 and carry out relevant clinical studies. Secondly, bone defect remodeling is a dynamic process involving osteogenesis (bone formation) and osteoclastogenesis (bone resorption).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a complex pathogenic metabolic disease ( Loffler et al, 2020 ; Zhang et al, 2022 ) caused by imbalanced bone formation and resorption ( Johnston & Slemenda, 1995 ; Gu et al, 2020 ). By 2050, the number of hip fracture patients in Asia will more than double, accounting for 50% of the total hip fracture in the world ( Wu et al, 2021 ).…”
Section: Osteoporosismentioning
confidence: 99%
“…We found that the number of articles in the past two or 3 years has increased significantly, as shown in the figure below ( Figure 1 ). The Wnt signaling pathway is believed to play an important role in bone homeostasis and bone related diseases, hence new osteoporosis therapies targeting Wnt signaling are emerging ( Manolagas, 2014 ; Zhang et al, 2022 ). Similarly, the protein kinase B (Akt) signaling pathway is closely associated with osteoporosis treatments ( Liu et al, 2018 ; Jiang et al, 2022 ).…”
Section: Osteoporosismentioning
confidence: 99%